How to Assess Fiscal Implications of Demographic Shifts : A Granular Approach - Amaglobeli, David (IMF How To Notes; How-To Note ;, 2016)
Over the next few decades, the world will experience significant demographic shifts, with material fiscal implications. In many advanced and emerging market economies, aging populations will lead to higher spending on pensions and health care. Moreover, projected population dynamics will adversely affect growth and government revenues. Building on and extending a 2015 IMF Staff Discussion Note by Clements and others, this note presents a simple framework that can assist researchers in quantifying the effects of demographic changes resulting from population aging on government fiscal balances. It includes two country applications of the framework and an associated template. The note addresses several key questions: What are channels through which demographic changes could affect public finances? How can we quantify the fiscal impact of demographic changes? How can we tailor the assessment to country-specific circumstances?